1994
DOI: 10.3171/jns.1994.80.3.0454
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic glial cysts of the pineal gland

Abstract: Small asymptomatic cysts of the pineal gland represent a common incidental finding in adults undergoing computerized tomography or magnetic resonance (MR) imaging or at postmortem examination. In contrast, large symptomatic pineal cysts are rare, being limited to individual case reports or small series. The authors have reviewed 24 cases of large pineal cysts. The mean patient age at presentation was 28.7 years (range 15 to 46 years); 18 were female and six male. Presenting features in 20 symptomatic cases inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
13

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 18 publications
0
48
0
13
Order By: Relevance
“…5 Over the subsequent years, sporadic reports of large symptomatic pineal cysts causing headache, Parinaud's syndrome, long tract signs, and pineal apoplexy appeared in the literature. 10,11,17,19,20,25 Although rare cases of pineal cysts continued to be reported, in nearly all cases the determination of "symptomatic" relied on signs of ventriculomegaly or Parinaud's syndrome. Klein and Rubinstein reported that among a surgical series of 7 symptomatic pineal cysts ranging in size from 1.0 to 4.5 cm, 5 patients demonstrated improvement following surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Over the subsequent years, sporadic reports of large symptomatic pineal cysts causing headache, Parinaud's syndrome, long tract signs, and pineal apoplexy appeared in the literature. 10,11,17,19,20,25 Although rare cases of pineal cysts continued to be reported, in nearly all cases the determination of "symptomatic" relied on signs of ventriculomegaly or Parinaud's syndrome. Klein and Rubinstein reported that among a surgical series of 7 symptomatic pineal cysts ranging in size from 1.0 to 4.5 cm, 5 patients demonstrated improvement following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]6,8,22 In rare cases, large cysts may obstruct the cerebral aqueduct, causing ventriculomegaly or compress the tectum, causing Parinaud's syndrome. 7,10,11,15,18,26 In our practice we have treated 3 patients who presented with hydrocephalus caused by compression of the aqueduct by a pineal cyst. While these findings are well-accepted indications for surgery, the majority of patients with pineal cysts do not present with these signs, and indications for intervention in these patients is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of these cysts are benign and are usually asymptomatic, some are occasionally associated with headaches, hydrocephalus, extraocular movement abnormalities and Parinaud's syndrome (2,3). The hemorrhage of a pineal cyst, which is sometimes referred to as pineal apoplexy, is considered to be rare and is often associated with severe symptoms (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…123 Rarely, large pineal cysts have also been associated with gaze palsy and Parinaud syndrome. 106,108,118,122,124,125 Although large cysts may be symptomatic, this occurrence is rare. The vast majority of even large cysts may be expected to present incidentally and remain asymptomatic.…”
Section: Pineal Cystsmentioning
confidence: 99%